The Role of Financial Literacy in the Early Childhood Education System Viewed from the Perspective of Sharia Economics: Case Study of Al Hikmah Kindergarten School, Kel. Pujidadi Binjai - Sahputri, Nur diah; Waqqosh, Abi (Law and Economics, 2025)
Early childhood education (ECE) plays a very important role in forming the basis of children's understanding of various aspects of life, including financial management. Financial literacy at the PAUD level is expected to instill the values of financial management in accordance with sharia economic principles, namely management that is fair, transparent, and free from elements of usury. This research aims to explore the role of financial literacy in the education system at Al Hikmah Kindergarten, Pujidadi Village, Binjai, and analyze it from an Islamic economic perspective. Through this case study, this research is expected to provide a deeper understanding of how financial literacy can be integrated in early childhood education in accordance with sharia principles